Reading border-crossing Japanese comics/anime in China: Cultural consumption, fandom, and imagination - Fung, Anthony and Pun, Boris and Mori, Yoshitaka (Global Media and China, 2019)
Differences in cultural consumption are well recognized as potential forces for changing the cultural identity of consumers. Based on this logic, our hypothesis posits that Chinese readers, who comprise the largest fan community of Japanese comics/anime, are culturally influenced by this foreign product. To examine this hypothesis, we question whether the global values and worldviews of freedom, peaceful coexistence, justice, companionship, and humanity, which are embedded in Japanese comics/anime, influence the values and ideology of Chinese readers. This study was aimed to examine the reading strategies and patterns in legally or illegally imported border-crossing cultural products to assess the potential cultural impact of their consumption on young Chinese readers. Their differences in passion could affect their devotion, their identity, and their worldviews. In this study, focus groups in Japan and China, in-depth interviews, and textual analyses of Japanese comic/amine were conducted to examine the reading, fandom, and cultural impact of comics/anime on Chinese urban youth. The significance of this study is that it explores new models of active reading that affect the long-term shape of and changes in the values and identities of Chinese youth. The findings of this study shed light on whether imported cultural products could transform, change, and dilute the ideologies of the state and nationalism, thereby allowing new and alternative imaginings of values and global citizenship, which are emerging areas of interest in global communication studies.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTE3Ny8yMDU5NDM2NDE5ODM1Mzc5